(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The right way out of the crisis of the agro-based industries is the maximum use of the opportunities of scientific and technological progress and the orientation of the real economy to innovative development. One of the promising technologies of crop production is an innovative technology in potato growing, which provides for the co-culturing of potatoes with honey crops. Phacelia tanacetifolia (PhaceliatanacetifoliaBenth) is selected as honey crop, which is a valuable green manure. It allows to reduce the need for organic and mineral fertilizers, increases the ecological cleanness of products, favors the growth of potato yield, provides the additional honey yield. Phacelia significantly improves the soil structure, displacing a significant part of weeds, providing natural loosening of the soil, protection from drying out, from pests and parasites. The co-culturing of potatoes with phacelia protects the environment from the use of dangerous plant protection products. If the economic effect is defined as the difference between the profits of innovative and traditional technologies, then, according to preliminary calculations, the level of profitability of innovative technology in potato growing is 1.9 times higher, and the profit from 1 ha is 1.6 times higher compared with the traditional technology. Large-scale development of the proposed technology is hampered by the lack of potato planters and seed planters, which provide planting of potatoes and sowing seeds of honey crops simultaneously, in the Russian market and the markets of the European Union. An innovative technology - mounted seeder for potato planters was developed by the staff members of the Pskov State University. The article describes the main agro-technological requirements to this device. A general model and a kinematic scheme were developed to visualize the combination of the working elements of the potato planter and the mounted seeder. The developed model falls into the type of seed planters, which is designed to sowing in drills the seeds of honey crops (phacelia) in the furrow between potatoes at the time of the forthcoming closing of this furrow by soil, and can be used in agricultural engineering. Potential consumers of the proposed innovative technology in potato growing and the developed mounted seeder are farm enterprises and agricultural production cooperatives, which have small plots of land, use crop rotation systems in potato growing, and work for reducing costs and increasing the yield of potato cultivation.